Клонування генів рекомбінантних субодиниць дифтерійного токсину Corynebacterium diphtheriae та їх експресія в клітинах Escherichia coli - Кабернюк, А.А.; Олійник, О.С.; Редчук, Т.А.; Романюк, С.І.; Колибо, Д.В.; Комісаренко, С.В. (Видавничий дім "Академперіодика" НАН України, 2008)
The diphtheria toxin is the main pathogen of Corynebacterium diphtheriae. This is a protein with molecular weight 58,360. Having penetrated into endosomes of sensitive cells, diphtheria toxin is digested into two subunits: A and B. Fragments of diphtheria toxin’s gene which encode subunits A and B have been amplified from genomic DNA of Corynebacterium diphtheriae strain NCTC 10648. Plasmids containing subunit A and subunit B have been constructed using expression vector pET24a. Expression of recombinant subunits was performed in E. coli strain Rosetta (DE3) сеlls under control of strong T7 promoter. Recombinant proteins were purified from cell lysate under denaturating conditions by affinity chromatography. Antigen properties were confirmed by western blot analysis.